Kepemimpinan Perempuan dalam Perspektif Al-Qur’an - Kamil, Kamil; Suriadi, Suriadi (Research and Development Institution, Darussalam Institute for Islamic Studies, 2021)
The issue of the status of women in Islamic studies is still interesting and inexhaustible and invites polemics. Historical facts prove that women were placed in an inferior position almost throughout Muslim history while men were in a superior position. It’s happening because of the interpretation of the Qur'an carried out by classical commentators who tend to be influenced by deeply entrenched patriarchal culture. In the view of a society that adheres to patriarchy, the view of subordinating women to male superiority is influenced by religious doctrine but if you look at the doctrine of Islam itself, it turns out that the idea of egalitarianism is highly upheld. Basically, the Qur'an provides an obvious justification for the equality of women with men but at the level of reality, it turns out that egalitarian ideas in the Qur'an often clash with public responses that tend to be biased.